A picture book of Jesse Owens - Adler, David A.; Casilla, Robert (New York : Holiday House, 1992)
A simple biography of the noted black track star who competed in the 1936 Berlin Olympics.
Keywords: Owens, Jesse, -- 1913-1980 -- Pictorial works -- Juvenile literature; Owens, Jesse, -- 1913-1980.; Track and field athletes -- United States -- Biography -- Pictorial works -- Juvenile literature; Track and field athletes; African Americans -- Biography; African American track and field athletes -- Biography -- Juvenile literature